Genome wide association analysis for grain micronutrients and anti-nutritional traits in mungbean [Vigna radiata (L.) R. Wilczek] using SNP markers - Kumar Sinha, Mayank; Aski, Muraleedhar; Mishra, Gyan Prakash; Kumar, M. B. Arun; Yadav, Prachi; P. Tokas, Jayanti; Gupta, Sanjeev; Pratap, Aditya; Agrawal, Shiv Kumar; Nair, Ramakrishnan; Schafleitner, Roland; Dikshit, Harsh (Frontiers Media, 2023)
Mungbean is an important food grain legume for human nutrition and nutritional food due to its nutrient-dense seed, liked palatability, and high digestibility. However, anti-nutritional factors pose a significant risk to improving nutritional quality for bio fortification. In the present study, genetic architecture of grain micronutrients (grain iron and zinc concentration) and anti-nutritional factors (grain phytic acid and tannin content) in association mapping panel of 145 diverse mungbean were evaluated. Based on all four parameters genotypes PUSA 1333 and IPM 02-19 were observed as desired genotypes as they had high grain iron and zinc concentration but low grain phytic acid and tannin content. The next generation sequencing (NGS)-based genotyping by sequencing (GBS) identified 14,447 genome-wide SNPs in a diverse selected panel of 127 mungbean genotypes. Population admixture analysis revealed the presence of four different ancestries among the genotypes and LD decay of ∼57.6 kb kb physical distance was noted in mungbean chromosomes. Association mapping analysis revealed that a total of 20 significant SNPs were shared by both GLM and Blink models associated with grain micronutrient and anti-nutritional factor traits, with Blink model identifying 35 putative SNPs. Further, this study identified the 185 putative candidate genes. Including potential candidate genes Vradi07g30190, Vradi01g09630, and Vradi09g05450 were found to be associated with grain iron concentration, Vradi10g04830 with grain zinc concentration, Vradi08g09870 and Vradi01g11110 with grain phytic acid content and Vradi04g11580 and Vradi06g15090 with grain tannin content. Moreover, two genes Vradi07g15310 and Vradi09g05480 showed significant variation in protein structure between native and mutated versions. The identified SNPs and candidate genes are potential powerful tools to provide the essential information for genetic studies and marker-assisted breeding program for nutritional improvement in mungbean.